2020
DOI: 10.1186/s12991-020-00266-7
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of the interpersonal and social rhythm therapy (IPSRT) in patients with bipolar disorder: results from a real-world, controlled trial

Abstract: Background: Bipolar disorder (BD) is one of the most burdensome mental disorder, with a lifetime prevalence of 2.4%, with a prevalence of 0.6% for bipolar type I and 0.4% for bipolar type II. Several interventions have been developed to implement the treatment strategy of bipolar disorder, including the Interpersonal and Social Rhythm Therapy (IPSRT). This intervention has been specifically developed to manage patients' stressful life events, improve the disruptions of social and circadian rhythms and increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 53 publications
(53 reference statements)
0
24
0
Order By: Relevance
“…IPSRT focuses primarily on stabilizing social rhythms such as eating regularly with other people and thus improving social interactions and relationships ( 75 ). Its efficacy has been proven multiple times ( 61 , 76 ). Interestingly, there is a renewing increase in awareness and clinical interest for therapy approaches taking the effects of regular daily structures and sleep hygiene into account ( 19 , 63 , 77 ).…”
Section: Discussionmentioning
confidence: 99%
“…IPSRT focuses primarily on stabilizing social rhythms such as eating regularly with other people and thus improving social interactions and relationships ( 75 ). Its efficacy has been proven multiple times ( 61 , 76 ). Interestingly, there is a renewing increase in awareness and clinical interest for therapy approaches taking the effects of regular daily structures and sleep hygiene into account ( 19 , 63 , 77 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most common psychosocial stressors that precede bipolar episodes are interpersonal conflicts. 27 Role-playing situations focusing on coping with criticism, underestimation, rejection, and acquiring assertive skills can help the patients increase their resilience to the psychosocial struggles and reduce the stress load that may trigger a future episode. 28 It is necessary to describe the challenging communication situations in detail, write down the communication sequences, and gradually practice alternative interactions.…”
Section: Basic Steps Of Schema Therapy In Bipolar Disordermentioning
confidence: 99%
“…Six studies reported on the administration of BLT as a treatment (47)(48)(49)(50)(51)(52), four on IPSRT (7,(53)(54)(55), two on blue-light blocking glasses (56)(57)(58), one on CBT-I (5), one on TSD (59), and four on combination treatments (60)(61)(62)(63). Most studies included both BD-I and II (n=9; 47%), followed by BD-I alone (n=6; 32%), and one study looked specifically at BD-II (5%).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Current treatment guidelines recommend pharmacological approaches as the first-line treatment (2,3). However, these approaches are only partially effective (4)(5)(6) and have varied acceptability rates (7,8).…”
Section: Introductionmentioning
confidence: 99%